Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/s23042155
|View full text |Cite
|
Sign up to set email alerts
|

Event-Guided Image Super-Resolution Reconstruction

Abstract: The event camera efficiently detects scene radiance changes and produces an asynchronous event stream with low latency, high dynamic range (HDR), high temporal resolution, and low power consumption. However, the large output data caused by the asynchronous imaging mechanism makes the increase in spatial resolution of the event camera limited. In this paper, we propose a novel event camera super-resolution (SR) network (EFSR-Net) based on a deep learning approach to address the problems of low spatial resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Asynchronous spatiotemporal pulse signals are presented as sparse discrete lattices in three-dimensional space in both time and space domains, which are more flexible in signal processing and feature expression than the traditional "image frame" paradigm, especially in the time domain length of the pulse signal processing unit or the choice of the number of pulses also increases the difficulty of inputting the visual analysis algorithm of asynchronous spatiotemporal pulse signals. Therefore, how to express the characteristics of asynchronous spatiotemporal pulse signals (Guo et al, 2023), as shown in Figure 10, mining the spatiotemporal characteristics of asynchronous spatiotemporal pulse signals for the visual analysis tasks of "high precision" and "high speed" is the most important method in the field of neuromorphic vision. Important and core research issues also determine the promotion and application of neuromorphic vision sensors.…”
Section: Characteristic Expression Of Asynchronous Spatiotemporal Pul...mentioning
confidence: 99%
See 3 more Smart Citations
“…Asynchronous spatiotemporal pulse signals are presented as sparse discrete lattices in three-dimensional space in both time and space domains, which are more flexible in signal processing and feature expression than the traditional "image frame" paradigm, especially in the time domain length of the pulse signal processing unit or the choice of the number of pulses also increases the difficulty of inputting the visual analysis algorithm of asynchronous spatiotemporal pulse signals. Therefore, how to express the characteristics of asynchronous spatiotemporal pulse signals (Guo et al, 2023), as shown in Figure 10, mining the spatiotemporal characteristics of asynchronous spatiotemporal pulse signals for the visual analysis tasks of "high precision" and "high speed" is the most important method in the field of neuromorphic vision. Important and core research issues also determine the promotion and application of neuromorphic vision sensors.…”
Section: Characteristic Expression Of Asynchronous Spatiotemporal Pul...mentioning
confidence: 99%
“…Deep learning method: The frequency accumulation image is input into the deep learning network based on "image frame". Lai Image representation of frequency accumulation of asynchronous pulse signal (Guo et al, 2023).…”
Section: Frequency Accumulation Imagementioning
confidence: 99%
See 2 more Smart Citations